2021
DOI: 10.1101/2021.03.31.21254494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interim report: Safety and immunogenicity of an inactivated vaccine against SARS-CoV-2 in healthy chilean adults in a phase 3 clinical trial

Abstract: Background: The ongoing COVID-19 pandemic has had a significant impact worldwide, with an incommensurable social and economic burden. The rapid development of safe and protective vaccines against this disease is a global priority. CoronaVac is a vaccine prototype based on inactivated SARS-CoV-2, which has shown promising safety and immunogenicity profiles in pre-clinical studies and phase 1/2 trials in China. To this day, four phase 3 clinical trials are ongoing with CoronaVac in Brazil, Indonesia, Turkey, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 16 publications
(2 reference statements)
0
63
1
1
Order By: Relevance
“… 30 In this study, T cell responses were not assessed, which was a limitation of the study design. However, a study in Chile found a significant induction of a T-cell response characterised by the secretion of interferon-gamma following vaccination of CoronaVac in a population aged 18 years and older, 19 , which was different from the lower response observed in our phase 1 trial among adults aged 18–59 years. 17 Another inactivated SARS-CoV-2 vaccine, BBV152, has also been reported to induced a Th1-biased response.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 30 In this study, T cell responses were not assessed, which was a limitation of the study design. However, a study in Chile found a significant induction of a T-cell response characterised by the secretion of interferon-gamma following vaccination of CoronaVac in a population aged 18 years and older, 19 , which was different from the lower response observed in our phase 1 trial among adults aged 18–59 years. 17 Another inactivated SARS-CoV-2 vaccine, BBV152, has also been reported to induced a Th1-biased response.…”
Section: Discussioncontrasting
confidence: 99%
“… 16 The analyses from phase 1–3 trials have shown that CoronaVac was effective, immunogenic, and safe in adults aged 18 years and older. 12 , 17 , 18 , 19 Furthermore, another 11 inactivated COVID-19 candidate vaccines are in clinical evaluation, and several studies have also shown that the inactivated vaccines can induce neutralising antibody responses and have good safety profiles. 20 , 21 , 22 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…CoronaVac study from Chile reported the seroconversion rate for the ≥60 years old group 18.1% after 14 days of the first dose, and 100% after 28 days of the second dose. 12 As mentioned by Grupper et al 13 age is an important factor in the humoral response induced after vaccination regardless of chronic medical conditions. We conclude that two doses of vaccination with CoronaVac were capable of induction humoral response in people over 60 years of age.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, we evaluated the exposure of receiving the first vaccine dose from 0 to 13 days before the sample collection date. An association during this period, where the vaccine likely has no or limited effectiveness, 4,20,21 may serve as an indicator of unmeasured confounding in the effectiveness estimate. The reference group for vaccination status was individuals who had not received a first vaccine dose before the date of sample collection.…”
Section: Discussionmentioning
confidence: 99%